Development of Students Worksheet Mathematics Based on Problem Based Learning (PBL) - Ningrum, Izza Eka; Suparman, S (Universitas Muhammadiyah Surakarta, 2018)
: Critical thinking skills must be part of student learning, and the school must be responsible for developing and evaluating critical thinking skills in the learning process. Efforts that can be made to improve critical thinking skills include promoting learning aids in the form of student-based problem-based learning worksheets. This study aims to design learning tools in the way student worksheets are based on problem-based learning. The method used in this study is the 4-D method which includes the stages of Define, Design, Development, and Disseminates. Data collection instruments in the form of expert validation instruments to measure validity as well as student questionnaires to measure practicality and obtain development product assessment from experts and students. The results of the validation data analysis by two validators stated that the validity level was 3.58 for the aspect of the worksheet content, the validity was 3.50 for the constructed aspect and 3.67 for the language aspect. This shows that the suitability of worksheets developed in all three elements of validation is good. After validation, the worksheets were tested on 23 VIII grade 2 students at Gunungkidul MTs, and the results of the trial said that the LKS received a good response from students and was practically used in the learning process of mathematics in the classroom.